2013
DOI: 10.1016/j.ymgme.2013.06.010
|View full text |Cite
|
Sign up to set email alerts
|

A somatic cell defect is associated with the onset of neurological symptoms in a lysosomal storage disease

Abstract: Mutations in individuals with the lysosomal storage disorder Niemann-Pick disease, type C1 (NPC1) are heterogeneous, not localized to specific protein domains, and not correlated to time of onset or disease severity. We demonstrate direct correlation of the time of neurological symptom onset with the severity of lysosomal defects in NPC1 patient-derived fibroblasts. This is a novel assay for NPC1 individuals that may be predictive of NPC1 disease progression and broadly applicable to other lysosomal disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 10 publications
1
13
0
2
Order By: Relevance
“…S2) in both tissues compared to controls. We have previously shown that higher levels of the well-known lysosomal marker LysoTracker are associated with NPC1 deficiency in fibroblasts and B cells of NPC1 patients (Rodriguez-Gil et al, 2013;te Vruchte et al, 2014). Similarly, primary fibroblasts derived from Npc1 em/em mutants showed significantly increased LysoTracker staining compared to controls (Fig.…”
Section: Generation Of Npc1 Em Micementioning
confidence: 65%
See 2 more Smart Citations
“…S2) in both tissues compared to controls. We have previously shown that higher levels of the well-known lysosomal marker LysoTracker are associated with NPC1 deficiency in fibroblasts and B cells of NPC1 patients (Rodriguez-Gil et al, 2013;te Vruchte et al, 2014). Similarly, primary fibroblasts derived from Npc1 em/em mutants showed significantly increased LysoTracker staining compared to controls (Fig.…”
Section: Generation Of Npc1 Em Micementioning
confidence: 65%
“…GSL accumulation in visceral and neuronal tissue, which has been associated with NPC1 (Maue et al, 2012;te Vruchte et al, 2004), also occurred in the brain and liver of Npc1 em/em mutants. In addition, elevated staining with the lysosomal marker LysoTracker is associated with NPC1 disease (Rodriguez-Gil et al, 2013;te Vruchte et al, 2014), and primary fibroblasts from Npc1 em/em mutants also showed increased LysoTracker staining. To the best of our knowledge, this is the first publication showing LysoTracker staining [measured by fluorescence-activated cell sorting (FACS)] in Npc1 mouse mutant fibroblasts derived from skin/ear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ген NPC1 (Gene ID 4864) имеет очень широкий спектр мутаций, отсюда нет возможности выявить четкую связь между уровнем мутации, клинической карти-ной, сроками манифестации болезни и тяжестью течения. Болезнь может манифестировать с неонатального периода до 39 лет [10]. NPC1-ген кодирует трансмембранный протеин, участвующий в интрацеллю-лярном транспорте холестерина.…”
Section: а в сunclassified
“…Накопление фибробластами неэстерифициро-ванного холестерина при болезни Ниманна -Пика, тип С1 (справа). Слева фибробласты кожи здорового человека [10] кальный паралич взора -на ранних стадиях болезни нередко не выявляется. За исключением перинатального периода системные проявления болезни выражены незначительно, с возрастом имеется тенденция к умень-шению спленомегалии.…”
Section: а в сunclassified